Juridical Analysis of Handling Homelessness and Beggar - Rahim, Arhjayati; Mustapa, Ira Suryani (SASI, 2022)
Introduction: This research analyzes how to handle homelessness and beggars in Gorontalo city either by Indonesian Criminal Code or by Regional regulation in Gorontalo city number 1 of 2018 concerning order and handling approach.Purposes of the Research: This research aims to study and analyze the handling of the homelessness and beggars in Gorontalo City using criminal code regulations and local regulations in Gorontalo City number 1 of 2018 about order and approaching handling.Methods of the Research: The method used in this research is the Sociological Juridicial Method The site of research was in Social and Society Empowerment Service of Gorontalo, the Municipal Police Government  service of Gorontalo, the Police station of Gorontalo city, the red light crossing of Baiturrahim Mosque in Gorontalo city, the crossing road of Gelael building, the Shopping center, central market, mall of Gorontalo, and Crossing road of Bunda Hospital, and some streets in Gorontalo city.Results of the Research: Handling process through Indonesian criminal code (KUHP) using quick investigation report, single law trial, the prosecutor is not mandatory to present/investigator can act as prosecutor in the court. Regional regulation number 1 of 2018 regulates two penalties: administrative (article 30) and criminal (article 32), preventive efforts in the form of emotional approach, coaching, making investigation report, and the last is returned to their respective place.